KELENGKAPAN INFORMASI MENGENAI CARA PENGGUNAAN PEAK FLOW METER YANG DIBERIKAN KEPADA PASIEN ASMA DI APOTEK - Amelia Lorensia; Doddy De Queljoe; Kristian Abram Santosa (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Measurement of lung fungction is a way to determine the effectiveness of a given therapy. A monitoring asthma symptoms is to see the value of peak expiratory flow (PEF) with a peak flow meter. The measurement is objective and can be used to predict the prognosis of asthma through the monitoring of conditions of the lung. This study aims to find out information on the use of a peak flow meter explanations given to the patient’s pharmacist in a pharmacy in a town in East Java. This research method is a non-experimental with cross sectional study. This study uses observation techniques in the form of a checklist, using the concept of a mysterious patient. Sampling by the proportional method, and then the data will be processed descriptively. The research sample of 80 pharmaceutical personnel consisting of 33 pharmacists and 47 non-pharmacists. In the group of non-pharmacists and pharmacists, the points most overlooked is the explanation of the recording of the results (number 6) and compared with the best value (number 8). Pharmacists still need to improve in understanding the basics and techniques in order to use a peak flow meter can help asthma patients to monitor their asthma medication